Kendala dan Peluang dalam Pendidikan Bahasa Arab Dasar: Perspektif Pengajaran dan Pembelajaran - Amali, Fatih Ridho; Hasan, Laili Mas Ulliyah (Prodi Pendidikan Keagamaan Islam, 2025)
This article explores barriers and opportunities in basic Arabic language education from the perspective of teaching and learning. Basic Arabic education is a very important early stage in Arabic learning that defines the foundations of student language skills. This article examines the various challenges faced in basic Arabic language teaching, including resource constraints, inefficient teaching approaches, and students' motivation issues. In addition, this article also discusses opportunities that can be exploited to improve the quality of basic arabic language education, such as the use of educational technology, innovative teaching methods, and a well-integrated curriculum. Research findings show that by identifying and overcoming obstacles and taking advantage of existing opportunities, basic Arabic language education can be significantly improved to support more effective and efficient learning.